Treatment De-escalation in Relapsing-Remitting Multiple Sclerosis: An Observational Study - Müller, Jannis; Sharmin, Sifat; Lorscheider, Johannes; Horakova, Dana; Kubala Havrdova, Eva; Eichau, Sara; Patti, Francesco; Grammond, Pierre; Buzzard, Katherine; Skibina, Olga; Prat, Alexandre; Girard, Marc; et al. (CNS drugs, 2025)
BACKGROUND: In relapsing-remitting multiple sclerosis (RRMS), extended exposure to high-efficacy disease modifying therapy may increase the risk of side effects, compromise treatment adherence, and inflate medical costs. Treatment de-escalation, here defined as a switch to a lower efficacy therapy, is often considered by patients and physicians, but evidence to guide such decisions is scarce. In this study, we aimed to compare clinical outcomes between patients who de-escalated therapy versus those who continued their therapy. METHODS: In this retrospective analysis of data from an observational, longitudinal cohort of 87,239 patients with multiple sclerosis (MS) from 186 centers across 43 countries, we matched treatment episodes of adult patients with RRMS who underwent treatment de-escalation from either high- to medium-, high- to low-, or medium- to low-efficacy therapy with counterparts that continued their treatment, using propensity score matching and incorporating 11 variables. Relapses and 6-month confirmed disability worsening were assessed using proportional and cumulative hazard models. RESULTS: Matching resulted in 876 pairs (de-escalators: 73% females, median [interquartile range], age 40.2 years [33.6, 48.8], Expanded Disability Status Scale [EDSS] 2.5 [1.5, 4.0]; non-de-escalators: 73% females, age 40.8 years [35.5, 47.9], and EDSS 2.5 [1.5, 4.0]), with a median follow-up of 4.8 years (IQR 3.0, 6.8). Patients who underwent de-escalation faced an increased hazard of future relapses (hazard ratio 2.36 and 95% confidence intervals [CI] [1.79-3.11], p < 0.001), which was confirmed when considering recurrent relapses (2.43 [1.97-3.00], p < 0.001). It was also consistent across subgroups stratified by age, sex, disability, disease duration, and time since last relapse. CONCLUSIONS: On the basis of this observational analysis, de-escalation may not be recommended as a universal treatment strategy in RRMS. The decision to de-escalate should be considered on an individual basis, as its safety is not clearly guided by specific patient or disease characteristics evaluated in this study.
Keywords: výsledek terapie; Multiple Sclerosis, Relapsing-Remitting; relabující-remitující roztroušená skleróza; Middle Aged; longitudinální studie; mužské pohlaví; ženské pohlaví; Longitudinal Studies; dospělí; retrospektivní studie; Humans; Adult; Female; Retrospective Studies; Treatment Outcome; lidé; Male; lidé středního věku